Management - Stoner, James Arthur Finch (Prentice Hall, 1989)
The best gets better! Ed Freeman brings his expertise on strategy and ethics to our best-selling Principles of Management Text. First management text with an AIE. Stoner is generally considered to be our highest level principles text, well-balanced and well-researched. Thoroughly fine tuned cutting edge classic video cases. New theme box on managing diversity.